The Daily Life of Lake Mareotis Therapeutae - Cardoso Bueno, Diego Andrés (ARYS. Antigüedad: Religiones y Sociedades, 2022)
Therapeutae constitute a Jewish ascetic community, made up of men and women, and established by Lake Mareotis on the outskirts of Alexandria. As Philo states in his treatise De vita contemplativa, its existence was centered on study, exegesis of sacred texts, and meditation and reflection. They also dedicate part of their time to the preparation of texts, hymns and diverse compositions dedicated to the Being. Retired from the world in their humble town leading a simple and secluded daily life, they compose a model of congregation consecrated to the contemplative life and to the service of God.
Keywords: Alexandria; contemplation; exegesis; Mareotis lake; sacred texts; therapeutae